Peran Sumber Daya Manusia dalam Struktur Lembaga Organisasi: (Laporan Hasil Kuliah Kerja Lapangan di DHD BPK Angkatan 45 Jawa Timur) - Adhiyaksa Rahman Buwana; I Gede Wiyasa (Jurnal Pengabdian Masyarakat, 2025)
The 45th Batch of Institution was established by the President of the Republic of Indonesia with the Decree of the President of the Republic of Indonesia Number 50 of 1984 as an institution engaged in the field of moral strength in order to preserve the Spirit, Spirit and Values of the 45th Struggle to the young generation of the nation's successors in filling the development after the Proclamation of Independence of the Republic of Indonesia on August 17, 1945. The Regional Daily Council of Batch 45 of East Java Province as an Organization of Batch 45 in the framework of its main task of preserving the soul, the Spirit of Value 45 to the components of the young generation of the people who fill independence, has the desire to remind all components of the nation's young generation as the next generation who will continue development in filling the independence of the Republic of Indonesia to understand the history and culture of the nation in a way that preserves the value of the struggle of the Indonesian nation at that time he was ready to sacrifice his life and body for the realization of an independent, united, just and prosperous Indonesian state as stated in the Preamble to the Constitution of the Republic of Indonesia. The 45th Batch Organization as an organization engaged in the field of Moral Force has an obligation and care to maintain the upright Unitary State of the Republic of Indonesia.